2012
DOI: 10.1007/s00586-012-2219-x
|View full text |Cite
|
Sign up to set email alerts
|

Posterior lumbar fusion by peek rods in degenerative spine: preliminary report on 30 cases

Abstract: The semi-rigid systems can now be considered a viable option in the lumbar degenerative disease, although clinical evaluations are necessary in the longer term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 11 publications
(16 reference statements)
2
27
0
3
Order By: Relevance
“…1,7,[22][23][24][25] However, clinical studies on the outcomes of patients who underwent spinal fusion with the PEEK rod pedicle screw system are limited, and their results are conflicting. 14,16,27 Therefore, the purpose of the current study was to evaluate the clinical and imaging outcomes of patients who underwent spinal fusion with PEEK rod constructs for lumbar spine disease. The current results indicated improved disability and pain scores, high fusion rates, and minor complications with no adjacent segment degeneration at the time of this writing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,7,[22][23][24][25] However, clinical studies on the outcomes of patients who underwent spinal fusion with the PEEK rod pedicle screw system are limited, and their results are conflicting. 14,16,27 Therefore, the purpose of the current study was to evaluate the clinical and imaging outcomes of patients who underwent spinal fusion with PEEK rod constructs for lumbar spine disease. The current results indicated improved disability and pain scores, high fusion rates, and minor complications with no adjacent segment degeneration at the time of this writing.…”
Section: Discussionmentioning
confidence: 99%
“…26 However, few clinical studies have been reported on PEEK rod pedicle screw spinal instrumentation systems, and those that were reported had small sample sizes and short-term follow-ups. 14,16,27 In addition, the reported results are conflicting; some studies reported good or excellent results with a low complication rate with PEEK rod systems, 16,27 whereas others reported a high reoperation rate with this system in patients with lumbar degenerative spine disease with no improved benefit over all-metal instrumented fusions. 14 To enhance the literature, the current article describes the authors' clinical results with the use of PEEK rods for posterior spinal fusion.…”
Section: A B E951mentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have documented the clinical outcomes of PEEK rods used for fusion [5]. De Iure et al [5] retrospectively reviewed 30 fusion cases in a single-cohort observational study with average follow-up of 18 months.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have documented the clinical outcomes of PEEK rods used for fusion [5]. De Iure et al [5] retrospectively reviewed 30 fusion cases in a single-cohort observational study with average follow-up of 18 months. All but one of the patients achieved satisfactory fusion, but the authors recommended longer follow up to better judge the effectiveness of PEEK rods for fusion.…”
Section: Introductionmentioning
confidence: 99%